Self-Scrutiny in Maimonides’ Ethical and Religious Thought - Bicknell, Jeanette (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2002)
AbstractSelf-scrutiny has long been considered necessary for the development of virtue. Maimonides’ insistence on the importance of self-scrutiny in the formation of character has its roots in Aristotle, but is developed by him in such a way as to be innovative. Three related themes are discussed here : Maimonides’ conception of the role self-scrutiny plays in moral development ; how the imperative of self-scrutiny shapes his analysis of Mosaic Law ; and the specifically religious function of self-scrutiny.